2015
DOI: 10.1158/0008-5472.can-14-2040
|View full text |Cite
|
Sign up to set email alerts
|

LASP1 Is a HIF1α Target Gene Critical for Metastasis of Pancreatic Cancer

Abstract: LASP1 is an actin-binding protein associated with actin assembly dynamics in cancer cells. Here we report that LASP1 is overexpressed in pancreatic ductal adenocarcinoma (PDAC) where it promotes invasion and metastasis. We found that LASP1 overexpression in PDAC cells was mediated by HIF-1α through direct binding to a hypoxia response element in the LASP1 promoter. HIF-1α stimulated LASP1 expression in PDAC cells in vitro and mouse tumor xenografts in vivo. Clinically, LASP1 overexpression in PDAC patient spec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
88
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 36 publications
0
88
0
Order By: Relevance
“…The final score was obtained by multiplying the intensity scores with staining range, and the results ranged from 0 to 9. For the final scores (intensity score  percentage score), scores less than 2 were considered as negative staining, 2-3 indicated weak staining, 4-6 was moderate staining, and >6 was strong staining (18). For the in vivo angiogenesis experiments, staining with CD34 was quantified on the basis of the intensity of microvessel staining in selected fields.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The final score was obtained by multiplying the intensity scores with staining range, and the results ranged from 0 to 9. For the final scores (intensity score  percentage score), scores less than 2 were considered as negative staining, 2-3 indicated weak staining, 4-6 was moderate staining, and >6 was strong staining (18). For the in vivo angiogenesis experiments, staining with CD34 was quantified on the basis of the intensity of microvessel staining in selected fields.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…LASP1 mRNA expression was a significant negative predictor of overall survival. LASP1 has been shown to promote invasion and metastasis; particularly, LASP1 overexpression in pancreatic ductal adenocarcinomas was found to be significantly associated with lymph node metastasis and poor overall survival [43]. Therefore, it is plausible that tumor-associated elevations in LASP1 may contribute to LVI, which could explain why we no longer observed a significant hazard ratio when a LASP1 cutoff of 2.1 was used and instead only LVI was found to be a significant predictor of overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia contributes to disease progression and promotes tumor growth and invasion, and clinical studies have shown that high levels of hypoxia directly correlate with a poor prognosis in pancreatic cancer (7). The observed correlation between tumor hypoxia and patient prognosis is ascribed to therapeutic failure and hypoxiainduced pro-metastatic potential, as several studies have shown that hypoxia stimulates a more invasive, metastatic phenotype via multiple mechanisms (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%